Ultrastructure of the ovariole sheath in Diatraea saccharalis (Lepidoptera : Pyralidae) - dos Santos, D. C.; Gregorio, E. A. (Inst Histol Embriol-conicet, 2002)
The ultrastructure of the ovariole sheath along the Diatraea saccharalis ovariole was studied by scanning and transmission electron microscopy. Each ovariole is surrounded by an epithelial sheath, a tunica propria and scattered lumen cells. These three components of the ovariole sheath show different ultrastructural features along the ovariole, in the germarium or in the vitellarium; these differences are more evident in the epithelial sheath cells. The epithelial sheath is composed by two layers of cells, the external one running longitudinally and the internal one running circularly in the ovariole. These cells, in vitellarium, present cytoplasmic bundles of myofilaments that are arranged parallel to the long axis of the cells; these myofilaments are apparently related to the contraction movements of the follicles within the ovariole. The acellular tunica propria, composed of finely filamentous material, is attached to the adjacent follicle cells by adhesive dense plates. Between the epithelial sheath and the tunica propria there is a population of lumen cells, with morphological features of secretory activity.
Keywords: epithelial sheath; tunica propria; lumen cells; electron microscopy